Enhancing Productive Capacities and Transforming Least Developed Country Economies Through Institution-building: Upcoming United Nations Conferences and the Way Forward - United Nations Conference on Trade; Development (United Nations, 2021)
In this policy brief, UNCTAD intends to shed light on the role of institutions in fostering productive capacities, and examines Institutions as one of the eight categories of the UNCTAD Productive Capacities Index. In the context of the formulation and implementation of policies and strategies in support of LDCs, recommendations are provided to support the building of stronger and more effective institutions, a prerequisite for fostering productive capacities.